2023
DOI: 10.1002/wrna.1827
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the CCR4‐Not complex in translation and dynamics of co‐translation events

Martine A. Collart,
Léna Audebert,
Martin Bushell

Abstract: The Ccr4‐Not complex is a global regulator of mRNA metabolism in eukaryotic cells that is most well‐known to repress gene expression. Delivery of the complex to mRNAs through a multitude of distinct mechanisms accelerates their decay, yet Ccr4‐Not also plays an important role in co‐translational processes, such as co‐translational association of proteins and delivery of translating mRNAs to organelles. The recent structure of Not5 interacting with the translated ribosome has brought to light that embedded info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 138 publications
0
1
0
Order By: Relevance
“…Additionally, we detect proteins required by early mosquito-stage parasites to become motile (IMC proteins and their regulators, CelTOS), adjust their surface protein composition (p25, p28, PSOPs, CPW-WPCs, CTRP, WARP, all known members of the crystalloid), develop the ability to evade mosquito immunity (P47, Cap380), and prepare for segmentation (basal complex members). We also detected an increased abundance of NOT5, which plays a role in engaging translating ribosomes encountering non-optimal codons in the A-site (39). Moreover, we observed that key components of the mitochondria are differentially abundant, including much of the respiratory chain (Complexes III, IV, and ATP synthase), and associated transporters required for their function are differentially abundant in zygotes, reflecting the need to rapidly adapt to the lower nutrient availability of mosquitoes.…”
Section: Resultsmentioning
confidence: 92%
“…Additionally, we detect proteins required by early mosquito-stage parasites to become motile (IMC proteins and their regulators, CelTOS), adjust their surface protein composition (p25, p28, PSOPs, CPW-WPCs, CTRP, WARP, all known members of the crystalloid), develop the ability to evade mosquito immunity (P47, Cap380), and prepare for segmentation (basal complex members). We also detected an increased abundance of NOT5, which plays a role in engaging translating ribosomes encountering non-optimal codons in the A-site (39). Moreover, we observed that key components of the mitochondria are differentially abundant, including much of the respiratory chain (Complexes III, IV, and ATP synthase), and associated transporters required for their function are differentially abundant in zygotes, reflecting the need to rapidly adapt to the lower nutrient availability of mosquitoes.…”
Section: Resultsmentioning
confidence: 92%